Mobile assembly of bricard linkages - Tan, Jia Yuan. (2011)
This project focuses on the mobile assembly of Bricard linkage, which combines mechanisms and attachments with the Bricard linkage while retaining deployability. Research on this project shows the application of the ideal Bricard linkage ability to have a non-stretchable membrane attached to it while maintaining its single deployment process, as well as to form a huge deployable structure by tiling.